HISTORICAL PERSPECTIVE OF CERVICAL CYTOLOGY: A REVIEW - Abid Rashid; Umbreen Naz; Adnan Sarwar et al. (Journal of University Medical & Dental College, 2017)
ABSTRACT: The research work on cervical cytology moved on a speed in 1920 after discovery of pap smear ndscreening by Papanicolaou. Cervical carcinoma, the 2 most common cancer worldwide in women, is found in all countries perspective of weather developed, under-developed or developing. Most women with cervical cancer and advanced disease result in low cure rates. Among diﬀerent risk factors of cervical carcinoma, the major ones include low socio economic and high parity status. Approximately two Lacs deaths occur per year due to cervical cancer accounting for 8.5% of all deaths in cancerous women worldwide. Majority of deaths can be prevented by screening program and training the patients when the disease is pre-invasive. A remarkable fall in mortality has been observed in regions where a comprehensive screening for CIN has been carried out.